Analisis pengelolaan wisata air terjun Kakek Bodo di Kelurahan Pecalukan Kecamatan Prigen Kabupaten Pasuruan - Andini, Neli; Kusufa, Roni Alam Ba'diya (Institute of Advance Science, Social, and Sustainable Future, 2024)
SWOT Analysis (SWOT Analysis) includes efforts to identify strengths, weaknesses, opportunities and threats that determine company performance. External information about opportunities and threats can be obtained from many sources, including colleagues at other companies. According to (Rangkuti 2004) explains that SWOT analysis is the systematic identification of various factors to formulate a company strategy. This analysis is based on logic that can maximize strengths and opportunities, but simultaneously minimize weaknesses and threats. The strategic decision making process is always related to the development of the company's mission, goals, strategies and policies. Therefore, strategic planning must analyze the company's strategic factors (strengths, weaknesses, opportunities and threats) in current conditions. This research uses a descriptive qualitative approach, as a scientific method often used by a group of researchers in the fields of social sciences and education. Qualitative research aims to gain knowledge through understanding and discovery. In qualitative research, the researcher is the key instrument, therefore the researcher must have theoretical provisions and broad insight so that he can ask questions, analyze and construct the object being studied more clearly. Based on the results of the processed data, the Grandfather Bodo Waterfall Tourism has a strength value of 3.58 which is very high compared to a weakness value of 2.53 and an opportunity value of 3.28 which is very high compared to a threat value of 2.89. Based on the results of the SWOT analysis diagram, the difference between strengths and weaknesses is 1.05, while the difference between opportunities and threats is 0.36. So the Y value is 1.05 and the X value is 0.36. From the results of the SWOT analysis, this tourism has great potential to be managed and developed, seen from the values of internal factors (strengths and weaknesses) and external factors (opportunities and threats). From the results of this analysis, the strength value is greater than the weakness value, as well as the opportunity value is greater than the threat value.